Hours Worked and the U.S. Distribution of Real Annual Earnings 1976–2016 - Iván Fernández-Val; Franco Peracchi; Aico van Vuuren; Francis Vella (Institute of Labor Economics (IZA), 2020)
We examine the impact of annual hours worked on annual earnings by decomposing changes in the real annual earnings distribution into composition, structural and hours effects. We do so via a nonseparable simultaneous model of hours, wages and earnings. We provide identification results and estimators of the objects required for the decompositions. Using the Current Population Survey for the survey years 1976–2016, we find that changes in the level of annual hours of work are important in explaining movements in inequality in female annual earnings. This captures the substantial changes in their employment behavior over this period. The impact of hours on males' earnings inequality operates only through the lower part of the earnings distribution and reflects the sensitivity of these workers' annual hours of work to cyclical factors.
Keywords: C14; I24; J00; 330; earnings inequality; sample selection; decompositions; nonseparable model